Implementasi Metode Think Pair Share (TPS) dalam Meningkatkan Hasil Belajar IPA Kelas VI SDN 03 Masbagik Selatan pada Semester I - Parhiah, Parhiah (TSAQOFAH, 2021)
The purpose of this study was to determine the implementation of the Think Pair Share (TPS) method in improving science learning outcomes in class VI students of SDN 03 Masbagik Selatan in the first semester of the 2019/2020 school year. The method of collecting data used in this research is the method of observation and tests. The results of the research show that the implementation of the Think, Pair, Share (TPS) method can improve students' science learning outcomes. This can be seen from the increase in the average value of student activities in each cycle. In the first cycle, the average score of students is 75 and classical completeness is 67%. In cycle II, the average value of student activity is 84 and classical completeness is 95%, so the Thin, Pair, Share method can improve science learning outcomes for sixth grade students at SDN 03 Masbagik Selatan in the first semester of the 2019/2020 school year.